2007
DOI: 10.1590/s0101-81752007000100021
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of eggs and immatures of Culex (Culex) saltanensis Dyar (Diptera, Culicidae) obtained in the laboratory and on the field

Abstract: The objectives of this morphometric study of Culex (Culex) saltanensis Dyar, 1928 larvae were to observe the continuous growth of siphon and cephalic capsule length and width in each instar, and to propose a linear equation to differentiate instars according to the size of both structures. Larvae obtained in laboratory at 27 ± 1ºC, photoperiod 14L:12D were studied. Larvae of the forth instar were collected on the field and compared with same instar larvae reared in the laboratory. Egg size and pigmentation pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The hatching rate of C. saltanensis larvae in the laboratory was 97.48% ± 2.32. Camargo et al (1994) found 93% for larvae of C. quinquefasciatus Say, 1823, a species that coexists with C. saltanenis in the natural environment (Zequi & Lopes 2007). Silva et al ( /1994 noted that temperature and humidity directly affect the life cycle of Aedes aegypti (Linnaeus, 1762) (Diptera, Culicidae) at 12L:12D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hatching rate of C. saltanensis larvae in the laboratory was 97.48% ± 2.32. Camargo et al (1994) found 93% for larvae of C. quinquefasciatus Say, 1823, a species that coexists with C. saltanenis in the natural environment (Zequi & Lopes 2007). Silva et al ( /1994 noted that temperature and humidity directly affect the life cycle of Aedes aegypti (Linnaeus, 1762) (Diptera, Culicidae) at 12L:12D.…”
Section: Discussionmentioning
confidence: 99%
“…After stabilization of the adult colony, eggs were collected from the pond every 15 days and added to the immature specimens obtained in the laboratory. The identification of the eggs followed the methods of Zequi & Lopes (2007). Eggs collected from the field were used for comparisons of oviposition in the field and laboratory.…”
Section: Methodsmentioning
confidence: 99%